Nutrition for the prevention and treatment of injuries in track and field athletes - Close, G. L.; Sale, G.; Baar, K.; Bermon, S. (International Journal of Sport Nutrition and Exercise Metabolism, 2019)
Injuries are an inevitable consequence of athletic performance with most athletes sustaining one or more during their athletic careers. As many as one in 12 athletes incur an injury during international competitions, many of which result in time lost from training and competition. Injuries to skeletal muscle account for over 40% of all injuries, with the lower leg being the predominant site of injury. Other common injuries include fractures, especially stress fractures in athletes with low energy availability, and injuries to tendons and ligaments, especially those involved in high-impact sports, such as jumping. Given the high prevalence of injury, it is not surprising that there has been a great deal of interest in factors that may reduce the risk of injury, or decrease the recovery time if an injury should occur: One of the main variables explored is nutrition. This review investigates the evidence around various nutrition strategies, including macro- and micronutrients, as well as total energy intake, to reduce the risk of injury and improve recovery time, focusing upon injuries to skeletal muscle, bone, tendons, and ligaments. Abstract from author